Peran Agama Sebagai Sarana Mengatasi Frustasi dan Depresi: Sebuah Telaah Psikologis - Aris Saefulloh (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
For religious people, the existence of a religion will affect the deepest side of them. Through deepunderstanding, a religion will guide them to find the solutions of any problem. The complexity of civilization has led to thecomplicated problems they faced. In reality, religion shows itself in many kinds of realities such as moral teachings, aqidah,belief, and movement, which have represented problems and social need of human beings. In fact, religion has a role ingiving solutions to spiritual problems. This article tries to explain how a religion takes role and functions in human life from apsychological point of view.